The Mirror : The Lost Bride Trilogy - Roberts, Nora (New York : St. Martin's Press, 2024)
Sonya MacTavish inherits a haunted Victorian mansion in Maine and is drawn to an antique mirror tied to dark family secrets. Transported to the past, she witnesses a bride$1 (Bs murder and uncovers a centuries-old curse. To break it, Sonya must solve the mystery before history repeats itself.s
Keywords: Mirrors -- Fiction; Inheritance and succession -- Fiction; Haunted places -- Fiction; Brides -- Fiction; Blessing and cursing -- Fiction; Haunted houses -- Fiction; Time travel -- Fiction; Maine -- Fiction; Paranormal fiction; Romance fiction